If you rearrange to make y the 'subject' to get by = -ax +c Then divide by b to get y alone y= -a/bx +c/b Then the gradient of the line is -a/b and it cuts the x axis at c/b That's what I remember anyway. (general equation of a line being y=mx +c where m is the gradient and c where it cuts the x-axis)
If you rearrange to make y the 'subject' to get
by = -ax +c
Then divide by b to get y alone
y= -a/bx +c/b
Then the gradient of the line is -a/b and it cuts the x axis at c/b
That's what I remember anyway. (general equation of a line being y=mx +c where m is the gradient and c where it cuts the x-axis)
rats I could kick myself, such a long time since I used that and as I was posting thought was it x or y axis. Of course if I'd taken a couple of seconds to try a couple of co-ords I'd have known better :-)